New insights in the mechanisms of opioid analgesia and tolerance: Ultramicronized palmitoylethanolamide down-modulates vascular endothelial growth factor-A in the nervous system - Laura Micheli; Stefania Nobili; Elena Lucarini; Alessandra Toti; Francesco Margiotta; Clara Ciampi; Daniel Venturi; Lorenzo Di Cesare Mannelli; Carla Ghelardini (Pharmacological Research, 2024)
Growing evidence suggests that opioid analgesics modulate angiogenesis during pathophysiological processes. Vascular endothelial growth factor-A (VEGF-A) was recently proposed to be involved in pain development. To date, no anti-angiogenic drug is used for pain management. When administered in a bioavailable formulation, (i.e., ultramicronized) N-palmitoylethanolamine (PEA) delays the onset of morphine tolerance, improves morphine analgesic activity and reduces angiogenesis in in vivo models. This study aimed at investigating whether VEGF-A is involved in PEA-induced delay of morphine tolerance. The anti-VEGF-A monoclonal antibody bevacizumab was used as a reference drug. Preemptive and concomitant treatment with ultramicronized PEA delayed morphine tolerance and potentiated the analgesic effect of morphine, while counteracting morphine-induced increase of VEGF-A in the nervous system. Similar results were obtained when bevacizumab was administered together with morphine. Of note, bevacizumab showed an analgesic effect per se. In equianalgesic treatment regimens (obtained through increasing morphine doses and associating PEA), PEA resulted in lower expression of VEGF-A in dorsal root ganglia (DRG) and spinal cord compared to morphine alone. Similar results were observed for plasma levels of the soluble VEGF receptor 1 (sFLT-1). Moreover, in morphine-treated animals, two pain-related genes (i.e., Serpina3n and Eaat2) showed a more than 3-fold increase in their expression at spinal cord and DRG level, with the increase being significantly counteracted by PEA treatment. This study supports the hypothesis that the effects of PEA on morphine analgesia and tolerance may be mediated by the down-modulation of VEGF-A and sFLT-1 in the nervous system and plasma, respectively.